Electrochemical Access to Aza‐Polycyclic Aromatic Hydrocarbons: Rhoda‐Electrocatalyzed Domino Alkyne Annulations. Issue 14 (28th January 2020) - Kong, Wei‐Jun; Shen, Zhigao; Finger, Lars H.; Ackermann, Lutz
Abstract: Nitrogen‐doped polycyclic aromatic hydrocarbons (aza‐PAHs) have found broad applications in material sciences. Herein, a modular electrochemical synthesis of aza‐PAHs was developed via a rhodium‐catalyzed cascade C−H activation and alkyne annulation. A multifunctional O‐methylamidoxime enabled the high chemo‐ and regioselectivity. The isolation of two key rhodacyclic intermediates made it possible to delineate the exact order of three C−H activation steps. In addition, the metalla‐electrocatalyzed multiple C−H transformation is characterized by unique functional group tolerance, including highly reactive iodo and azido groups. Abstract : Electrochemical access to aza‐polycyclic aromatic hydrocarbons (aza‐PAHs) was achieved via rhoda‐electrocatalyzed domino C−H functionalization. A multifunctional O ‐methylamidoxime facilitates the high chemo‐ and regioselectivity. The obtained aza‐PAHs and their derivatives have potential applications in catalysis, optoelectronics, and energy storage.